Acute Kidney Injury among Neonates with Perinatal Asphyxia in a Tertiary Care Centre - Arun Giri; Sunil Kumar Yadav; Vijay Kumar Shah (Journal of Nepal Medical Association, 2024)
Introduction: Perinatal asphyxia is a very common cause of morbidity and mortality in both term and preterm neonates and ranks the second most important cause of neonatal death. The incidence and importance of acute kidney injury in the neonatal period are becoming increasingly apparent. Early diagnosis and timely management of acute kidney injury is very important in these newborns to avoid other long-term adverse events. This study aimed to find out the prevalence of acute kidney injury among neonates with perinatal asphyxia in a tertiary care centre.